2022
DOI: 10.1186/s12887-021-03077-1
|View full text |Cite
|
Sign up to set email alerts
|

Cue-based feeding and short-term health outcomes of premature infants in newborn intensive care units: a non-randomized trial

Abstract: Background Feedings based on behavioral cues is a method relying on infants’ behavioral expressions of readiness to feed. The objective of this interventional study was to determine the effect of cue-based feeding on the short-term health outcomes of preterm infants. Methods This quasi-experimental study utilized a historical or phase lag design. It involved 60 preterm infants admitted to an Iranian referral hospital’s Level III-Newborn Intensive C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
0
9
0
7
Order By: Relevance
“…[16,20] Cue-based feeding has shown to have positive effects on short-term health outcomes in infants, demonstrating greater weight gain, fewer oxygen desaturations, and decreased frequency of gavage feeding events. [21] Several quality improvement (QI) initiatives have been implemented in NICUs with emphasis on cue-based feeding, and a systematic review of the QI initiatives concluded that weight gain, time to full oral feedings, and hospital length of stay may be improved. [22] This approach also allows for early identi cation of infants at risk for a delay in the achievement of feeding independence in order to implement tailored and developmentally appropriate interventions to succeed in the PO feeding.…”
Section: Discussionmentioning
confidence: 99%
“…[16,20] Cue-based feeding has shown to have positive effects on short-term health outcomes in infants, demonstrating greater weight gain, fewer oxygen desaturations, and decreased frequency of gavage feeding events. [21] Several quality improvement (QI) initiatives have been implemented in NICUs with emphasis on cue-based feeding, and a systematic review of the QI initiatives concluded that weight gain, time to full oral feedings, and hospital length of stay may be improved. [22] This approach also allows for early identi cation of infants at risk for a delay in the achievement of feeding independence in order to implement tailored and developmentally appropriate interventions to succeed in the PO feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo 23 objetivou investigar o efeito da contenção facilitada sobre a dor neonatal durante a amostragem de sangue na punção do calcanhar. Este é um ensaio clínico cruzado que foi realizado em 40 recémnascidos prematuros.…”
Section: Contenção Facilitadaunclassified
“…Estudos 24,25 associaram a contenção facilitada determinando o seu efeito na redução da dor dos prematuros nos procedimentos invasivos. Pesquisas 23,25 identificaram que há necessidade de investigação e aprofundamento em relação a contenção facilitada.…”
Section: Estímulos De Organização E Aconchegounclassified
See 2 more Smart Citations